2015
DOI: 10.1038/ijo.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor deficiency protects mice from diet-induced adiposity and metabolic disorders through increased energy expenditure

Abstract: BACKGROUND/OBJECTIVES Epidemics of obesity and diabetes are escalating. High-calorie/high-fat food is a major cause for these global health issues, but molecular mechanisms underlying high-fat, diet-induced obesity are still not well understood. The aryl hydrocarbon receptor (AhR), a transcription factor that acts as a xenobiotic sensor, mediates environmental toxicant-induced obesity, insulin resistance and development of diabetes. AhR also influences lipid metabolism and diet-induced obesity. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
119
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 38 publications
12
119
1
Order By: Relevance
“…These data are consistent with results from mice with adipocyte-specific deficiency in AhR, where mice displayed increased body weight, fat mass, AT inflammation, and decreased glucose tolerance compared to wild type mice when fed a high fat diet (39). In direct contrast, it was recently reported that high-fat fed mice with whole body deficiency of AhR were protected from obesity, insulin resistance, and adipose inflammation (430). In another study, aged, but not young mice with whole body AhR deficiency were reported to have impaired glucose tolerance compared to wild type controls, without concomitant differences in body weight between genotype (46).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…These data are consistent with results from mice with adipocyte-specific deficiency in AhR, where mice displayed increased body weight, fat mass, AT inflammation, and decreased glucose tolerance compared to wild type mice when fed a high fat diet (39). In direct contrast, it was recently reported that high-fat fed mice with whole body deficiency of AhR were protected from obesity, insulin resistance, and adipose inflammation (430). In another study, aged, but not young mice with whole body AhR deficiency were reported to have impaired glucose tolerance compared to wild type controls, without concomitant differences in body weight between genotype (46).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 98%
“…AhR is expressed in adipocytes (354), and the adipocyte AhR has recently garnered increased attention for its role not only in the xenobiotic response of AT, but also as a regulator of body weight, fat mass, and lipid homeostasis (194) (39) (430). Several studies provide evidence of AhR-mediated regulation of AT function, but results have not been consistent.…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…It is well established that obesity [2] and associated complications [3, 4] develop differently between males and females; and that gene expression profiles in liver and adipose tissue are dissimilar in male and female mice [5]. Given that the aryl hydrocarbon receptor (AHR) has a large role in obesity in male mice [68], we asked whether the AHR carries out a similar role in obesity for females.…”
Section: Introductionmentioning
confidence: 99%
“…These studies and recent work with B6. Ahr −/− mice, which were shown to be resistant to obesity [7, 8, 23], indicated key roles for the AHR in fat metabolism and deposition as well as a possible target for AHR-based therapeutic and preventative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of lipid metabolism leading to hepatic steatosis and insulin resistance suggests that the AHR plays an important role in integrating exogenous and endogenous influences in lipid and energy metabolism [22, 23]. Findings from AHR-deficient mice show that, like GF mice [24, 25], they are protected from high fat diet-induced obesity, hepatic steatosis, and insulin resistance [26]. …”
Section: Introductionmentioning
confidence: 99%